The obstacle race: the fortunes of women painters and their work - Greer, Germaine (Farrar, Straus, Giroux, 1979)
If men and women are equally capable of genius, why have there been no female artists of the stature of Leonardo, Titian or Poussin? In seeking to answer this question, Germaine Greer introduces us to major but underestimated figures in the history of Western painting–Angelica Kauffmann, Natalia Goncharova, Suzanne Valadon, Berthe Morisot, Kathe Köllwitz–and produces a brilliantly incisive and richly illustrated study. She explains the obstacles as both external and surmountable and internal and insurmountable in the race for achievement.
Section: 373 pages
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; arts; cours; discipline; discours dominant; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; périodes historiques; régions; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théorie de l'art

Originals: American women artists - Munro, Eleanor C. (Simon and Schuster, 1979)
Discusses the lives and work of Mary Cassatt, Georgia O'Keefe, Alice Neel, Louise Nevelson, Helen Frankenthaler, Elaine de Kooning, Sylvia Stone, and other American women artists
Keywords: 1900-1999; Biography; amériques; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Les femmes : caste, classe ou sexe opprimé - Reed, Evelyn (Féminisme et socialisme aux États-Unis. Textes du Parti socialiste des travailleurs, 1979)
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; classe sociale; cours; fem1000; histoire et politique; militance; mouvements des femmes*; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis

Women & art: a history of women painters and sculptors from the renaissance to the 20th century - Fine, Elsa Honig (Allanheld & Schram/Prior, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques

Capitalisme, Patriarcat et ségrégation professionnelle des sexes - Hartmann, Heidi; Coryell, Rosette (Questions Féministes, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; angleterre; approches et analyses; capitalisme; corps; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Macmillan, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Histoire du feminisme français : du moyen âge à nos jours - Albistur, Maite; Armogathe, Daniel (Des femmes, 1977)
« Il s’agit de faire toute la lumière possible, en l’état actuel des connaissances, sur une protestation aussi ancienne que la pensée, mais régulièrement déjouée par les pièges de l’imaginaire masculin et du discours dominant. » Cette « querelle » des femmes a été analysée selon quatre temps forts : le temps du féminisme élitaire (du VIe siècle à 1789) ; une période de féminisme en mouvement (1789-1871) ; un temps de féminisme bourgeois et réformiste (1871-1945) ; enfin, une période de féminisme radical, inaugurée par Simone de Beauvoir dans Le Deuxième Sexe (1949). « C’est au total quinze siècles d’une autre histoire qui se déroulent sous nos yeux dans ces 500 pages d’analyse patiente, une histoire tour à tour sereine et passionnée, grave et légère, besogneuse et festive, une histoire arrachée aux pesanteurs des mythes, des doutes et de la mauvaise foi. » M.A. et D.A.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; approches et analyses; conditions des femmes*; cours; cycles supérieurs; discipline; droits des femmes*; europe; fem1000; fem7000; france; histoire; histoire du féminisme; histoire et politique; lit3220; moyen-âge; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques

Nos amis et nous. Les fondements cachés de quelques discours pseudo-féministes - Delphy, Christine (Questions Féministes, 1977)
https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/40619102?searchText=&searchUri=&ab_segments=&searchKey=&refreqid=fastly-default%3A6014802099e05df5c356ea4e8a4a2b55&seq=9
Keywords: 1900-1999; 1970-1979; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; inégalités; militance; patriarcat; premier cycle; pédagogie; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques

Mère de tant d'enfants - Obamsowin, Alanis (1977)
Dans son premier long métrage documentaire, sorti en 1977, Alanis Obomsawin rend hommage à la place centrale des femmes et des mères dans les cultures amérindiennes. Album de témoignages féminins autochtones, le film dépeint ces cultures matriarcales fortes, auxquelles on a tenté d'imposer pendant des siècles des habitudes et coutumes étrangères. Suivant le cycle de la vie des femmes autochtones de la naissance à la vieillesse en passant par l'enfance, la puberté, l'âge adulte et la maturité, il montre comment ces femmes se sont battues pour retrouver un sentiment d'égalité, inculquer la fierté de leur culture à leurs enfants et transmettre leurs histoires aux nouvelles générations.
Keywords: amériques; approches et analyses; cours; documentaire; fem3100; femmes* autochtones; histoire et politique; premier cycle; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques

The Destruction of American Indian families - Unger, Steven (Association on American Indian Affairs, 1977)
Responding to the need for a comprehensive source of information regarding the separation of American Indian children from their families, this book presents essays which: examine the Indian child-welfare crisis in contemporary, legal, and historical perspectives; document the human cost of the crisis to Indian parents, children, and communities; and report on innovative programs designed and implemented by the Indian tribes themselves. Specifically, this book includes the following sections and essay titles: (1) Contemporary Overviews ("The Destruction of American Indian Families" and "The Role of the Federal Government: A Congressional View"); (2) Historical Perspectives ("The Effects of Boarding Schools on Indian Family Life: 1928" and "'Kid Catching' on the Navajo Reservation: 1920"); (3) The Human Cost ("'The Drunken Indian': Myths and Realities"; "The Wasted Strengths of Indian Families", "The Human Cost of Removing Indian Children from Their Families", "Child-Welfare Services to Indian People in the Albuquerque Area", "Indian Child Welfare in Oregon", "The Ravage of Indian Families in Crisis", "The Question of Best Interest", and "The Placement of American Indian Children–The Need for Change"); (4) A Legal Perspective ("Parent and Child Relationships in Law and in Navajo Custom"); (5) Tribal Actions ("Indian Children and Tribal Group Homes: New Interpretations of the Whipper Man" and "Tribal Resolutions"). (JC)
Keywords: american indian families; amériques; approches et analyses; autochtones; cours; discipline; droit; famille; his4443; histoire et politique; premier cycle; racisme; racisme systémique; residential schools; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violence systémique; violences; états-unis

From the center: feminist essays on women's art - Lippard, Lucy R. (E.P. Dutton, 1976)
Lucy Lippard is both one of our finest critics of contemporary art and one of the most perceptive and strongest supporters of women artists. These thirty essays, written since the publication of Changing in 1971, delineate the growth of Lippard's feminism and the present status of women's art. In Lippards words: "...while I wish I could claim that this book established a new feminist criticism, all I can say is that it extends the basic knowledge of art by women, that it provides the raw material for such a development." From the Center is important, stimulating reading for all concerned with the women's art movement.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; théorie de l'art; états-unis

Women artists: recognition and reappraisal from the early Middle Ages to the twentieth century - Petersen, Karen; Wilson, J. J. (Harper & Row, 1976)
Commentary on and photographs of sculpted and painted images of women created by women shed light upon feminine self-perceptions and the contributions of women artists through the centuries
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Conclusion. Conscience des femmes, monde de l'homme. - Rowbotham, Sheila (Conscience des femmes, monde de l'homme, 1976)
Dans la première partie de son essai, Sheila Rowbotham dit très concrètement à partir de son expérience personnelle, qui est aussi celle de toute la génération d’avant 1968, comment elle a pris conscience de son oppression et commencé à lutter. Du maquillage aux rêves, de la mode au militantisme, dans un monde créé par les hommes et pour l’homme, les femmes ont compris qu’elles étaient exclues, reléguées dans les rôles de mères et d’épouses, envers des rôles masculins dominants. Elle approfondit ensuite cette analyse dans la seconde partie en montrant la fonction particulière des rôles « féminins » dans le système capitaliste. Par le sous-paiement des emplois, le non-paiement du travail domestique et la reproduction qu’elles assurent, les femmes sont exploitées économiquement, idéologiquement et sexuellement. Et si cette situation prouve que le pouvoir capitaliste et le pouvoir masculins sont liés, c’est bien contre elle que les femmes se sont mises à lutter ensemble.
Translators: _:n15666
Keywords: 1900-1999; 1970-1979; approches et analyses; classe sociale; conflit; cours; division sexuelle du travail; fem1000; histoire et politique; militance; patriarcat; premier cycle; périodes historiques; systèmes d'oppressions; thématiques; travail

Women painters of the world: from the time of Caterina Vigri, 1413-1463, to Rosa Bonheur and the present day - Sparrow, Walter Shaw (Hacker Art Books, 1976)
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques

Brouillon pour un dictionnaire des amantes - Wittig, Monique; Zeig, Sande (Grasset, 1976)
"Si vous manque l'imagination de ce que peuvent être les amantes dont parle ce Dictionnaire, il vous suffit d'y rechercher le terme. N'hésitez pas en recopier la définition comme je le fais ici : Les amantes sont celles qui, éprouvant un violent désir les unes pour les autres, vivent/aiment dans des peuples, suivant les vers de Sappho, "en beauté je chanterai mes amantes". Il serait difficile de faire plus clair, plus concis et plus élégant. Quelque chose pourtant vous chiffonne (vous constatez d'ailleurs que le mot "chiffon" est absent de ce dictionnaire) : la définition que vous venez de lire est subtilement circulaire et pleinement plurielle. Littré, Larousse, Robert ne procèdent pas ainsi : lexicographes positifs, ils nous enseignent entre autres choses positives, qu'une amante est une femme attachée à un homme par des sentiments tendres ; qu'au pluriel, le terme, dès lors nécessairement masculin (les amants) désigne un couple s'aimant d'amour réciproque. Or, les amantes de Wittig et Zeig vivent non en couples, mais en formation immédiatement politique (des peuples) et plurielle. Enfin, les amantes ne sont pas des femmes, et encore moins des femmes qui aiment des femmes. — Comment ça !? les amantes ne sont pas des femmes ?!
Keywords: amour lesbien; approches et analyses; discours dominant; histoire et politique; lesbianisme; personnes lesbiennes; sexisme; sexualité; systèmes d'oppressions; systéme hétérosexuel; thématiques

A history of women artists: [Every art form-pottery, weaving, painting, graphics, sculpture, photography, from prehistoric times to the present] - Munsterberg, Hugo (C. N. Potter : distributed by Crown Publishers, 1975)
A history of women artists : [Every art form-pottery, weaving, painting, graphics, sculpture, photography, from prehistoric times to the present]
Keywords: arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

Women in the fine arts, from the seventh century B.C. to the twentieth century A.D - Clement, Clara Erskine (Hacker Art Books, 1974)
"WOMEN IN THE FINE ARTS FROM THE SEVENTH CENTURY B.C. TO THE TWENTIETH CENTURY" by Clara Erskine Clement is a historical account written in the early 20th century. The book surveys the contributions of women artists throughout history, spanning over two millennia and across multiple cultures. It aims to highlight women's roles and achievements in the fine arts, pointing out that many artists have been overlooked or forgotten despite their significant contributions. The opening of the book introduces the author's mission to gather information about women artists by reaching out to them directly, thus establishing a foundation of credibility and thoroughness for her work. Clement mentions that over a thousand women artists have been identified for this study, sharing intriguing fragments of history, such as those of ancient Greek and Roman women artist names and highlighting the cultural shifts that impacted their careers. It also critiques the lack of recorded contributions from women in the arts before the Renaissance, outlining the challenges they faced throughout different eras while paving the way for future generations of female artists. The opening sets the stage for a deeper exploration of women's artistic heritage in the following chapters. (This is an automatically generated summary.)
Keywords: arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

Pédagogie des opprimés suivi de Conscientisation et révolution - Freire, Paulo (François Maspero, 1974)
Ouvrage majeur de Paulo Freire, ce livre présente quelques aspects d’une pédagogie élaborée non seulement pour les opprimés, mais avec eux, et dans le cadre même de leur lutte perpétuelle pour affirmer leur humanité.
Première publication : 1970 https://web-s-ebscohost-com.proxy.bibliotheques.uqam.ca/ehost/detail/detail?vid=0&sid=4d2dddbb-6f04-4611-9d00-4774e074bd61%40redis&bdata=Jmxhbmc9ZnImc2l0ZT1laG9zdC1saXZl#AN=3149227&db=nlebk
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem7000; histoire et politique; inégalités; justice sociale; militance; pédagogie; ressource en ligne; systèmes d'oppressions; thématiques; éducation

Our hidden heritage: five centuries of women artists - Tufts, Eleanor (Paddington Press, 1974)
Our hidden heritage: five centuries of women artists unearths an unheralded legacy of art treasures by women artists. THrough individual biographies, the lives and work of twenty-two women artists are authoritatively described by Eleanor Tufts. These exciting portrayals provide new insights into the lives and works, the frustrations and successes of these talented women, as well as into their relationships with their contemporaries, husbands, freinds and families. Over 125 full-page reproductions of their works from major collections throughout the world demonstrate the variety and enduring quality of their art. Their lives and their work were as diverse as their cultures and their times.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques

Un groupe de femmes de Montréal - Un groupe de femmes québécoises. (Manifeste des femmes québécoises, 1971)
Keywords: 1900-1999; 1970-1979; EDI; amériques; approches et analyses; conflit; cours; fem1000; groupes communautaires; histoire et politique; justice sociale; militance; mouvements féministes; premier cycle; périodes historiques; québec; régions géographiques; thématiques

The politics of housework - Mainardi, Patricia; New England Free Press (New England Free Press, 1970)
https://caringlabor.wordpress.com/2010/09/11/pat-mainardi-the-politics-of-housework/
Keywords: 1900-1999; 1970-1979; amérique du nord; amériques; approches et analyses; care; cours; discipline; féminisme marxiste; histoire et politique; inégalités; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique; états-unis

Essays on sex equality. - Mill, John S.; Mill, Harriet H.; Rossi, Alice S. (The University of Chicago Press, 1970)
Ce volume rassemble pour la première fois tous les écrits de John Stuart Mill et Harriet Taylor Mill sur l'égalité entre les sexes, dont _The Subjection of Women_ de John Stuart Mill, un classique de l'histoire du mouvement des droits des femmes depuis sa publication il y a cent ans depuis. Ce volume contient également un important essai d'interprétation d'Alice S. Rossi sur Mill et Harriet Taylor qui décrit et analyse leur longue relation personnelle et intellectuelle.
Keywords: 1800-1899; EDI; approches et analyses; cours; fem1000; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; systèmes d'oppressions; thématiques